Transcriptional Mechanisms of Drug Addiction - Nestler, Eric J. (Korean College of Neuropsychopharmacology, 2012)
Regulation of gene expression is considered a plausible mechanism of drug addiction given the stability of behavioral abnormalities that define an addicted state. Numerous transcription factors, proteins that bind to regulatory regions of specific genes and thereby control levels of their expression, have been implicated in the addiction process over the past decade or two. Here we review the growing evidence for the role played by several prominent transcription factors, including a Fos family protein (ΔFosB), cAMP response element binding protein (CREB), and nuclear factor kappa B (NFκB), among several others, in drug addiction. As will be seen, each factor displays very different regulation by drugs of abuse within the brain's reward circuitry, and in turn mediates distinct aspects of the addiction phenotype. Current efforts are geared toward understanding the range of target genes through which these transcription factors produce their functional effects and the underlying molecular mechanisms involved. This work promises to reveal fundamentally new insight into the molecular basis of addiction, which will contribute to improved diagnostic tests and therapeutics for addictive disorders.